CONCENTRATING SOLAR POWER (CSP) IN MALAYSIA ENVIRONMENT : A REVIEW - Ab Ghani, Mohd Ruddin; Gan, Chin Kim (2012)
Malaysia has abundant of solar energy with magnitude of approximately 4.21-5.56 kWhm-2 for average daily solar irradiations and the sunshine duration is more than 2,200 hours per year. However, until now Malaysia is only focusing on Photovoltaic (PV) panel to generate electricity, while harnessing solar energy by using Concentrating Solar Power (CSP) has not been given adequate consideration by the government. This paper reviews the CSP technology and the potential of developing CSP plant in Malaysia environment by considering the Direct Normal Irradiance (DNI) and a few geographical aspects.